2003
DOI: 10.1080/09593330309385651
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous control of metals and organics using a fluidized bed adsorber

Abstract: A previous study has examined the performance of a fluidized activated carbon adsorber for removal of organics and particulate emissions from an incinerator under various fluidized operating conditions. The results show that it is an effective control device to treat the organics and coarse particles. However toxic heavy metal compounds cannot be completely destroyed during the incineration process and will volatilize at high temperature and then condense to form metallic particulates during the cooling of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Due to its high heating value, high mass transfer and the ability of continuous operating and capturing harmful material, the fluidized bed reactor has been gradually applied on incineration process. In previous study, fluidized bed could control the pollutants such as acid gases [1], organic compounds [2,3], heavy metals [2] and particulates [3,4] during incineration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high heating value, high mass transfer and the ability of continuous operating and capturing harmful material, the fluidized bed reactor has been gradually applied on incineration process. In previous study, fluidized bed could control the pollutants such as acid gases [1], organic compounds [2,3], heavy metals [2] and particulates [3,4] during incineration.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticles are very small and the diffusion mechanism dominates, so the fluidized bed can capture nanoparticles. In the authors' earlier works, the fluidized bed was used to remove acid gas, organic compounds and heavy metals [12][13][14]. A series studies also focused on the filtration of the fly ash of a coalfired power plant and a municipal solid waste incinerator by fluidized beds [15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…According to these studies, solid sorbents are used to capture heavy metals through two mechanisms: chemical adsorption and physical deposition during incineration processes. On the other hand, fluidized bed adsorber also provides good performance for heavy metals control [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Scrubbing technology, such as wet scrubbing, semi-dry scrubbing and dry scrubbing, is used to reduce acid gases in incineration systems [34]. Previous studies have demonstrated the effective control of acid gases like SO 2 and HCl by using fluidized bed adsorber, spray dryer and fabric filter in series [22,27,28,34,35]. Applying catalyst to oxidize or reduce the acid gases is in practice due to its high removal efficiency (above 90%) [31,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%